HEMŞİRE ADAYLARINDA SOSYAL MEDYA BAĞIMLILIĞI İLE BESLENME BİLGİSİ VE BAZI DEĞİŞKENLER ARASINDAKİ İLİŞKİNİN DEĞERLENDİRİLMESİ. - Çelik, Özge Mengi; Duran, Sedef (Karya Journal of Health Science, 2022)
Objective: Social media can affect individuals' nutritional knowledge and behaviors positively and negatively. In this study, it was aimed to investigate the relationship between social media addiction and nutritional knowledge and some variables in nurse candidates. Method: This descriptive study was carried out with 391 volunteers between the ages of 18-25, studying at Trakya University, Faculty of Health Sciences, Department of Nursing. Demographic characteristics, anthropometric measurements, nutritional habits, social media usage habits, social media addictions, nutritional knowledge levels and physical activity levels of individuals were questioned through the questionnaire form. Individuals' nutritional knowledge levels were determined by the 'Nutrition Knowledge Level Scale for Adults (NKLSA)', their social media addictions by the 'Social Media Addiction Scale-Adult Form (SMAS-AF)' and their physical activity levels with the 'International Physical Activity Assessment Questionnaire Short Form (IPAQ-short form)'. The data obtained from the study were evaluated using the SPSS (Statistical Package for Social Science) 22.0 statistical package program. Results: The rate of students who did not follow social media tools was 12.8%. Of the people most followed on social media on nutrition/diet, 66.8% were dietitians, and 9.7% were doctors. 29.2% of the students had bad, 35.3% moderate, 27.6% good, 7.9% very good basic nutrition knowledge levels; 25.1% had bad, 22.3% medium, 23.5% good, 29.2% very good knowledge about food preferences. A statistically significant positive correlation was found between SMAS-AF total score and NKLSA total score and basic nutritional knowledge score (p<0.05). There was a negative correlation between SMAS-AF total score and age; a positive correlation was found between the total score of the NKLSA and age and grade of education (p<0.05). Conclusion: It was seen that most of the nurse candidates did not have sufficient nutrition knowledge. It was determined that as the use of social media increased, the nutritional knowledge levels of the nurse candidates also increased.